2011
DOI: 10.1021/es1034427
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Decomposition of New and Unknown Polar Brominated Disinfection Byproducts during Chlorination

Abstract: Brominated disinfection byproducts (Br-DBPs) are generally more cytotoxic and genotoxic than their chlorinated analogues. A great portion of total organic bromine in chlorinated drinking water is still unknown and may be ascribed to polar Br-DBPs. In this work, a novel approach, precursor ion scan using ultra-performance liquid chromatography/electrospray ionization-triple quadrupole mass spectrometry, was adopted and further developed for selective detection and identification of polar Br-DBPs, which made it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
207
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 266 publications
(220 citation statements)
references
References 19 publications
13
207
0
Order By: Relevance
“…It was concluded that the Ho fraction with phenolic hydroxyl and conjugated double bonds was responsible for the production of trichloromethanes and trichloroacetic acids. The above conclusion may be supported by some recent reports, in which some aromatic halogenated DBPs are found to be actual intermediate DBPs that can decompose to form commonly known DBPs including HAAs and THMs [33][34][35].…”
Section: Ft-ir and 13 C Cpmas Nmr Spectroscopy Analysis Of Nomsupporting
confidence: 64%
“…It was concluded that the Ho fraction with phenolic hydroxyl and conjugated double bonds was responsible for the production of trichloromethanes and trichloroacetic acids. The above conclusion may be supported by some recent reports, in which some aromatic halogenated DBPs are found to be actual intermediate DBPs that can decompose to form commonly known DBPs including HAAs and THMs [33][34][35].…”
Section: Ft-ir and 13 C Cpmas Nmr Spectroscopy Analysis Of Nomsupporting
confidence: 64%
“…Recently, Zhang et al 11 successfully developed the PIS method using ESI-tqMS for fast selective detection of polar Br-DBPs and studied the formation of new and unknown Br-DBPs during chlorination. 23 They detected 38 ion clusters of possible Br-DBPs, five of which were confirmed or proposed as brominated acetic acids, 11 could be confirmed or proposed to be identified chemical structures, and 22 were bromine-containing compounds with unknown molecular formula. Because their samples were prepared using a liquid−liquid extraction method and the formulas of most of Br-DBPs in their study are not available, a comprehensive comparison was difficult.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The concentration and property of NOM influence water quality directly, because NOM is considered as the major precursor for many disinfection by-products (DBPs) in water treatments [3,4].…”
Section: Introductionmentioning
confidence: 99%